Anisotropic Synthetic Allomelanin Materials via Solid‐State Polymerization of Self‐Assembled 1, 8‐Dihydroxynaphthalene Dimers. Issue 32 (24th June 2021) - Zhou, Xuhao; Gong, Xinyi; Cao, Wei; Forman, Christopher J.; Oktawiec, Julia; D'Alba, Liliana; Sun, Hao; Thompson, Matthew P.; Hu, Ziying; Kapoor, Utkarsh; McCallum, Naneki C.; Malliakas, Christos D.; et al.
Abstract: Melanosomes in nature have diverse morphologies, including spheres, rods, and platelets. By contrast, shapes of synthetic melanins have been almost entirely limited to spherical nanoparticles with few exceptions produced by complex templated synthetic methods. Here, we report a non‐templated method to access synthetic melanins with a variety of architectures including spheres, sheets, and platelets. Three 1, 8‐dihydroxynaphthalene dimers (4‐4′, 2‐4′ and 2‐2′) were used as self‐assembling synthons. These dimers pack to form well‐defined structures of varying morphologies depending on the isomer. Specifically, distinctive ellipsoidal platelets can be obtained using 4‐4′ dimers. Solid‐state polymerization of the preorganized dimers generates polymeric synthetic melanins while maintaining the initial particle morphologies. This work provides a new route to anisotropic synthetic melanins, where the building blocks are preorganized into specific shapes, followed by solid‐state polymerization. Abstract : A new method to achieve synthetic melanin materials with various well‐defined architectures, ranging from spheres to anisotropic sheets and ellipsoidal platelets, is described. The specific shapes are obtained through pre‐organizing the building blocks of melanins, followed by solid‐state oxidative polymerization to render polymeric materials without changing the overall morphology.